Do functional mobility tests predict the risk of falls in community-dwelling elderly? - Moreira, Ana Carolina Silva de Souza; Mazo, Giovana Zarpellon; Hauser, Eduardo; Paiva, Paula Bertolini de; Menezes, Enaiane; Cardoso, Fernando Luiz (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: The falls are associated with morbidity and mortality in the elderly. Numerous of functional mobility clinical tests have been created to identify older adults with potential for risk of falls. Objective: The purpose of this systematic review was to determine the predictive validity of functional mobility tests to predict the risk of falls in community-dwelling elderly. Method: Articles in English were searching in MEDLINE, SCOPUS and CINAHL. We found 18,520 documents and, after applying the inclusion and exclusion criteria, 11 articles were part of the final analysis. All articles analyzed included subjects over 60 years old. Results: The results showed that the TUG Test has good discriminative validity for elderly non-institutionalized, but it does not provide an adequate predictive validity. The TUG Test may not be enough as a unique basic screening tool to detect the risk of elderlies´ falling. Conclusion: It is suggested that the TUG Test should be used in combination with other predictors of falling risk tools or should it be reconfigured for the different levels of elderly physical active functionality.